Campur Kode dalam Pembelajaran di Kelas Rendah Sekolah Dasar Negeri 74 Rejang Lebong - Agustina Haryani Putri; Dian Eka Chandra Wardhana; Supadi Supadi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The purpose of this study was to describe the form of code mixing, the type of mixed code, and the factors causing the code mixing process in learning activities in the low-grade classes of SD Negeri 74 Rejang Lebong. This research uses descriptive method. The data source in this study was the teacher's language when interacting with students in the lessons in grade one, two, and three at 74 Rejang Lebong Elementary School. The data in this study are in the form of teacher speech during interaction with students which contain mixed codes in learning in grades one, two, and three at 74 Rejang Lebong Elementary School. The data steps in this study were recording and interviewing. The data analysis steps in this study were (1) data transcription, (2) data identification, (3) data classification, (4) data interpretation, (5) data conclusion. The results of this study indicate that the form of word code mix includes the form of verbs, nouns, adjectives, adverbs, pronouns, conjunctions, interrogative, demonstrative, numeralia. Meanwhile, the form of verb phrases, nouns, pronouns, adverbs, numeralia, interrogative, and demonstrative. The mixed types of code in low grade learning include the mixed types of code in, and mixed types of code out, as well as mixed types of code. The code-mixing event came from the Indonesian language which was inserted in English. Mix code into sourced from regional languages ​​and mix code mix sourced from regional languages ​​and English. The factors causing the code include function and purpose factors, speech partners, speaker and the speaker's personality.